Ab-initio evaluation of acid influence on chemical stability of hydrophilic diglycolamides - Luštinec, Jakub; Koubský, Tomáš; Kalvoda, Ladislav (Frontiers in Molecular Biosciences, 2022)
Diglycolamides (DGA) form one of the most promising groups of organic ligands used in bio-inspired solvent extraction processes of lanthanide and actinide ions. Continuous experimental and theoretical research is still performed in order to further improve their application properties including their chemical stability in the real extraction environment. This work provides results of our theoretical approach focused on inclusion of an acid influence on the DGAs chemical structure, treated in frame of the density functional theory. Three different models describing the acid action are proposed and investigated in attempt to increase the resulting accuracy of the chemical stability predictions based on verified theoretical descriptors. The procedure is applied and tested on the set of selected hydrophilic DGA representatives. Comparison of the model results obtained with and without acid action shows that two types of protection effects may occur: a ‘direct’ protection, accompanied by an explicit change of the ligand stability indicators, and an ‘indirect’ one consisting in reaction of acid molecules with radicals preceding the contact of latter with the extracting ligands. The possibility of the direct acid protection route is supported by the significant decrease of the Fukui charges found with the acid models included. On the other hand, there is in general no significant difference of trends in the calculated chemical stability descriptors suggesting that an indirect mechanism must be also considered in order to explain the experimentally observed protective role of acids on the chemical stability of investigated DGA derivatives.